ANALYSIS OF LUBRICATION CONDITIONS FOR ANGLE PLANETARY GEARBOXES APPLIED IN MINING SCRAPER CONVEYORS - Andrzej WIECZOREK (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents calculations of the relative oil film value for the meshing of angle planetary gearboxes used in mining scraper conveyors. Calculating the value of this parameter was made using methodology that was compliant with ISO/TR 15144-1: 2014 (E). As a result of the analysis, it was found that exploitation of mining gears takes place under boundary or mixed lubrication conditions, with oil viscosity and surface roughness having a significant influence on these conditions.